Nursing of a patient with postoperative pain of total knee replacement and renal insufficiency treated with Huolong cupping therapy (火龙罐治疗全膝关节置换术后疼痛伴肾功能不全1例护理体会) - LI Fei (李菲); CAO Haiyan (曹海燕); YANG Aiguo (杨爱国) (中西医结合护理)
This paper summarized the clinical nursing experience of treating a patient with postoperative pain of total knee arthroplasty and renal insufficiency using Huolong cupping therapy. After the Traditional Chinese Medicine syndrome differentiation, comprehensive nursing interventions such as emotional care, daily living guidance and dietary regulation were carried out. In addition, Huolong cupping therapy was applied to relieve the clinical symptoms, and emphasis was placed on protecting the patient's renal function. After the adjuvant treatment with Huolong cupping therapy, the patient's knee pain was significantly relieved, the joint mobility function improved, the renal function remained stable, and the quality of life was enhanced. (本文总结火龙罐治疗1例全膝关节置换术后疼痛伴肾功能不全患者的临床护理经验。基于中医辨证施护理论和护理评估, 制定个体化护理方案, 在情志护理、生活指导、饮食调护、康复指导等常规护理基础上开展火龙罐辅助治疗, 并注重对患者肾功能的保护。经综合干预, 患者膝关节疼痛有效减轻, 焦虑情绪缓解, 关节活动功能得到改善, 肾功能保持稳定, 生活质量显著提高。)